Qual o valor da expressão (-1) elevado a 0 + (-6) ÷ (-2) -24 ????
Soluções para a tarefa
Respondido por
4
Boa noite.
![(-1)^0 + (-6) : (-2) -24
1 + 3 - 24 =
4 - 24 = 20
(-1)^0 + (-6) : (-2) -24
1 + 3 - 24 =
4 - 24 = 20](https://tex.z-dn.net/?f=%28-1%29%5E0+%2B+%28-6%29+%3A+%28-2%29+-24+%0A%0A1+%2B++3+-+24+%3D+%0A%0A4+-+24+%3D+20+%0A%0A)
Regras dos sinais:
+ com + = +
- com - = +
- com + = -
+ com - = -
Bons estudos! :-)
Regras dos sinais:
+ com + = +
- com - = +
- com + = -
+ com - = -
Bons estudos! :-)
Perguntas interessantes
Matemática,
11 meses atrás
História,
11 meses atrás
História,
11 meses atrás
Administração,
1 ano atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás